High discordance between punch biopsy and excision in establishing basal cell carcinoma subtype: analysis of 500 cases. (3rd July 2012) - Wolberink, E.A.W.; Pasch, M.C.; Zeiler, M.; van Erp, P.E.J.; Gerritsen, M.J.P.
Abstract: Background Basal cell carcinoma (BCC) is the most frequently occurring cancer in humans. Worldwide incidences rise about 10% each year, increasing the burden on dermatologists, general practitioners and pathologists as well as increasing costs for the health care system. Increasingly non‐surgical treatment options are used in the treatment of BCC, without histological confirmation of BCC subtype, potentially resulting in under‐treatment. Objective We evaluated the diagnostic accuracy of a punch biopsy for the BCC histological subytpe in a primary BCC and the prevalence of biopsy‐based under‐diagnosis of aggressive subtypes. Accuracy of a punch biopsy was defined as concordance of the diagnosis of subtype of BCC at punch biopsy and excision. Methods A retrospective chart‐review was performed of primary BCC, which were proven by punch biopsy and subsequently treated by excision. The first 100 consecutive BCCs per year during the years 2004–2009 were included, yielding a total of 500 evaluated BCCs. Results The overall accuracy of punch biopsy for BCC subtype at excision was 69%, in single‐type BCC 83% ( n = 343) and in mixed‐type BCC 37% ( n = 157). Accuracy varied substantially according to BCC subtype, being highest in the superficial subtype (84%) and subsequently in infiltrative (69%), nodular (63%) and micronodular subtype (38%). In 11% of all cases, an unsuspected more aggressive subtype was present. Conclusion Punch biopsy has a high accuracy in single‐type BCCs and a considerably lower accuracy in mixed‐type BCCs for establishing BCC subtype compared to excision. The presence of an unsuspected aggressive subtype could explain therapy failure of non‐surgical treatments like imiquimod or photodynamic therapy.